Survei Pemanfaatan Informasi Radio Prambors Terhadap Data Informasi Jurnalistik Mahasiswa - Najwa Malikah; Wahyunengsih (CV. Multi Kreasi Media, 2023)
In the midst of the onslaught of technological advances, radio continues to grow listener growth. In Indonesia, Jakarta is the city with the most listeners in the past year. Radio is one of the media preferred by the Indonesian people for entertainment and information. Information is a basic element implied in the concept of planned use. The familiar characteristic of radio (emotional attachment) conveys a feeling of listening to information and entertainment. Apart from prioritizing entertainment broadcasts, radio in Jakarta is now continuing to work on journalistic programs in the form of inserts. With the times and the development of the arrival of television media, radio has slowly changed, but radio still has a place in the hearts of its audience. The audio nature of radio allows other activities of its viewers at the same time. Among the dozens of radio stations in Jakarta, there are eight major radio stations that regularly broadcast news and entertainment flashes. One of them is Prambros, a radio station that still exists and is popular today, namely Prambros Radio. The purpose of this study is to analyze the use of mass media as student information data through Prambros Radio. It was concluded that Prambors Radio played a very important role in disseminating information to the public,